EFL Teachers’ Practices and Perspectives on Learner Autonomy in Virtual Language Learning Environments in Jordan - Naima Ahmad Al-husban; Mohammad Tawalbeh (International Journal of Language Education, 2023)
The current study investigated EFL teachers’ perspectives and practices regarding learner autonomy in the virtual language learning environment in Jordan. An interview and observation checklist have been used to collect data. Ten EFL teachers have been interviewed and one recording of their classes has been observed. Results revealed that teachers were aware of the psychological and they employed some strategies reflecting their views. Unlike the psychological perspective, the political perspective was not seen in EFL teachers’ practices. However, EFL teachers did believe in their importance. Based on the result, enhancing the pedagogy of autonomy should be a priority of policymakers while strategizing future plans. Besides, the national curriculum should provide teachers with the freedom to enhance learner autonomy. Further research should be conducted using a wider sample, and including further variables.